Promoter Hypermethylation Analysis of Host Genes in Cervical Cancer Patients With and Without Human Immunodeficiency Virus in Botswana - Tawe, Leabaneng; Grover, Surbhi; Zetola, Nicola; Robertson, Erle S.; Gaseitsiwe, Simani; Moyo, Sikhulile; Kasvosve, Ishmael; Paganotti, Giacomo M.; Narasimhamurthy, Mohan (Frontiers in Oncology, 2021)
Background: Epidemics of human immunodeficiency virus (HIV) and cervical cancer are interconnected. DNA hypermethylation of host genes' promoter in cervical lesions has also been recognized as a contributor to cervical cancer progression. Methods: For this purpose, we analyzed promoter methylation of four tumor suppressor genes (RARB, CADM1, DAPK1 and PAX1) and explored their possible association with cervical cancer in Botswana among women of known HIV status. Overall, 228 cervical specimens (128 cervical cancers and 100 non-cancer subjects) were used. Yates-corrected chi-square test and Fisher's exact test were used to explore the association of promoter methylation for each host gene and cancer status. Subsequently, a logistic regression analysis was performed to find which factors, HIV status, high risk-HPV genotypes, patient's age and promoter methylation, were associated with the following dependent variables: cancer status, cervical cancer stage and promoter methylation rate. Results: In patients with cervical cancer the frequency of promoter methylation observed was greater than 64% in all the genes studied. The analysis also showed a higher risk of cervical cancer according to the increased number of methylated promoter genes (OR=6.20; 95% CI: 3.66–10.51; P<0.001). RARB methylation showed the strongest association with cervical cancer compared to other genes (OR= 15.25; 95% CI: 6.06–40.0; P<0.001). Cervical cancer and promoter methylation of RARB and DAPK1 genes were associated with increasing age (OR=1.12; 95% CI: 1.01-1.26; P=0.037 and OR=1.05; 95% CI: 1.00-1.10; P=0.040). The presence of epigenetic changes at those genes appeared to be independent of HIV status among subjects with cervical cancer. Moreover, we found that cervical cancer stage was influenced by RARB (χ2=7.32; P=0.002) and CADM1 (χ2=12.68; P=0.013) hypermethylation, and HIV status (χ2=19.93; P=0.001). Conclusion: This study confirms the association between invasive cervical cancer and promoter gene methylation of tumor suppressing genes at the site of cancer. HIV infection did not show any association to methylation changes in this group of cervical cancer patients from Botswana. Further studies are needed to better understand the role of HIV in methylation of host genes among cancer subjects leading to cervical cancer progression.